Genus Plesiommata Provancher (Hemiptera: Cicadellidae) in Argentina: first detailed description of the female genitalia and comparisons with its neotropical congeners - Defea, Bárbara Soledad (2017)
Plesiommata Provancher is a sharpshooter genus with six species described, three present in the Neotropics. The morphology of the female genitalia of this genus is still poorly known. In this contribution, the female genitalia of P. mollicella (Fowler) and P. corniculata Young are described and illustrated for the first time. The vector species P. corniculata Young is recorded as new for Argentina. A key to Neotropical species including new female genital characters is presented along with updated information as new distribution records, host plant records and phytosanitary importance.